Mechanical Properties of Fireclay Bricks from Binaliw Clay - Dominic Baygan, Gabriel; Abellana, Virglio (Asian Review of Mechanical Engineering, 2022)
Binaliw clay, considered to be local waste from crushing and quarrying operations, was utilized to produce fireclay bricks. The chemical and mineralogical composition of the raw material were determined through various tests. Clay samples were prepared by milling, sieving, molding, drying, and sintering from 8000C to 11000C at 1000C intervals for 2 hours. Mechanical properties such as cold crushing strength, volume firing shrinkage, apparent porosity, and bulk density were identified through the appropriate ASTM standards. It was found out that the aforementioned properties, except apparent porosity, increased with increasing temperature- apparent porosity decreased on the contrary. The polymorphic transformations of kaolin and quartz to mullite and cristobalite supported the trends of the mechanical properties at increasing temperatures. However, the values attained in this study were ineligible for classification according to ASTM C27-98 due to the values being lower than the stipulated requirement. Nevertheless, the researchers believe that through a refinement of the manufacturing processes and an addition of additives, Binaliw clay could be a feasible raw material for the production of fireclay bricks.